Livestock for Sale Animal Husbandry in a Roman Frontier Zone - Groot, Maaike (Amsterdam Archaeological Studies, 2016)
The civitas Batavorum was a settlement on the north-western frontier of the Roman Empire, and it is now the site of numerous archaeological excavations. This book offers the most up-to-date look yet at what has been discovered, using the newest archaeological techniques, about the town and its economy, its military importance, and the religious and domestic buildings it held. It will be essential reading for anyone studying the economy of the Roman provincial countryside or the details of food supply for the Roman army and town.